(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
In medicine, the field of anesthesiology is an integral part of surgical practice. The success of any operation process directly depends not only on the qualified and responsible work of the doctors. Today, the rapid development of medical technologies, the widespread introduction of a new generation of anesthesia aparats require high technical knowledge, accuracy and responsibility from technical nurses. Improper Organization of the work of technical nurses or poor control pose a risk to the life of the patient, may be the reason for the interruption of the operational process.